Praying to Poshamma is for good fortune, not religion - Subadra, Joopaka (Prabuddha: Journal of Social Equality; Vol 4 No 1 (2020): Dedicated to Thanthai Periyar, 2020)
This interview was conducted in Hyderabad, India, in September 2019. Joopaka Subadra is a poet, writer, critic and a very significant figure in the Dalit movement. Here she talks about her views on literature and the alien concept of religion for her community. She dwells on the simplistic formulation of patriarchy by the mainstream, for her, hunger is patriarchy and is more violent than any other form.